Counter-narratives: Rizpah and the comfort women' statue - Joo, Samantha (Journal for the study of the Old Testament, 2019)
Contextual hermeneutics allows interpreters to read the Bible from their location. However, interpreters not only read meaning into the text, as a number of scholars claim, but in the process, they actually illuminate the original context underlying the text. To demonstrate this point, I will be analyzing the story of Rizpah through the lens of a current event, the Japanese government's efforts to remove the comfort women' bronze statues in Korea. The bronze statues embody counter-narratives that challenge and ultimately threaten the master narrative of the Japanese government. Likewise, Rizpah who stands on a boulder also functions as a counter-monument against King David. She resists the royal historian's effort to whitewash David's involvement in the murder of the Saulide descendants. However, to understand the specific way in which Rizpah challenges the royal court propaganda, it is necessary to engage critical methods of reading.